Dampak Pembangunan Jalan Tol Trans Jawa terhadap Pertumbuhan Ekonomi di Jawa Tengah: Institut Pertanian Bogor - Fahmi salam Ahmad (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2022)
Road infrastructure as an element in transportation services is an important element in supporting mobility in the economic, social and cultural fields. One of the road infrastructures, namely toll roads, are built with the aim of increasing the efficiency of distribution services in order to support economic growth in order to realize the equitable development and the stability in regional development. This study analyzes the impact of the construction of Trans Java toll road on the economic growth of districts/cities in Central Java, one of the provinces crossed by this toll road. The analytical tool used is panel data regression. The results of the analysis show that the existence of toll roads increases economic growth in the districts/cities they pass through. Therefore, the agenda for expanding the coverage of districts/cities covered by toll roads in Central Java needs to be continued in order to support the stable and equitable development. Meanwhile, other factors such as human resources and the contribution of the agricultural sector also affect economic growth.